In vitro expression of rat lens aldose reductase in Escherichia coli. - Old, S E (1990)
Aldose reductase (alditol:NADP+ oxidoreductase, EC 1.1.1.21), an enzyme that converts glucose to sorbitol, the first step of the polyol pathway, has been implicated in secondary complications of diabetes, such as cataracts, retinopathy, neuropathy, and nephropathy. Aldose reductase inhibitors have been observed to prevent or delay the onset of these complications; however, more potent and specific inhibitors are needed. Development of new inhibitors necessitates a better understanding of the molecular structure of this protein. To elucidate the structure-function relationships of aldose reductase and to develop methods of regulating this enzyme, large and homogeneous quantities of rat lens aldose reductase have been expressed in bacterial cells. A construction of the complete coding sequence and 3' untranslated region for rat lens aldose reductase was assembled in the expression vector pKK233-2 (Pharmacia). This construction expresses an active enzyme that has been purified and demonstrates kinetic, immunological, and inhibitory properties similar to rat lens aldose reductase.